2008
DOI: 10.1002/adma.200800452
|View full text |Cite
|
Sign up to set email alerts
|

Smooth‐Morphology Ultrasensitive Solution‐Processed Photodetectors

Abstract: Solution-processed optoelectronic materials offer a route to low-cost photodetectors, large-area solar cells, and integrated optical sources. [1][2][3] While significant progress has been reported in organic and polymer spin-cast optoelectronics, colloidal quantum dots offer a distinct further advantage -the convenient tuning of absorption onset via the quantum size effect. [4] Electronic transport has recently been enhanced in sizeeffect-tuned colloidal quantum dot films using ligand exchange, resulting in ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 12 publications
(22 reference statements)
1
43
0
Order By: Relevance
“…The development of colloidal QD solar cells has benefitted further from postdeposition ligand exchange by thiols, which was used in order to avoid excessive aggregation of the PbS QDs, which occurred when the ligand exchange was performed in solution. 18 Moreover, Seo et al 19 previously reported an improvement of photovoltaic performance (energy efficiency (PCE)) of a P3HT/PbS device to 0.01% employing post-deposition ligand exchange using short-length ligands as acetic acid. Post-deposition ligand exchange with bifunctional linker molecules such as ethanedithiol and 1,4-benzenedithiol have also been used recently.…”
Section: Introductionmentioning
confidence: 99%
“…The development of colloidal QD solar cells has benefitted further from postdeposition ligand exchange by thiols, which was used in order to avoid excessive aggregation of the PbS QDs, which occurred when the ligand exchange was performed in solution. 18 Moreover, Seo et al 19 previously reported an improvement of photovoltaic performance (energy efficiency (PCE)) of a P3HT/PbS device to 0.01% employing post-deposition ligand exchange using short-length ligands as acetic acid. Post-deposition ligand exchange with bifunctional linker molecules such as ethanedithiol and 1,4-benzenedithiol have also been used recently.…”
Section: Introductionmentioning
confidence: 99%
“…2. The Sargent group were early pioneers of photodetector devices based on PbS NCs, [20][21][22][23][24][25] though earlier to this photovoltaic devices based on PbS NCs had also been the focus of research attention. 26,27 Following early reports of ultrasensitive PbS NC based photoconductor devices 21,22 there has been a rapid development of many aspects to understand and improve performance.…”
Section: Pbs Nanocrystal Photodetectorsmentioning
confidence: 99%
“…Ligand exchange can also be undertaken in the solution phase prior to depositing the PbS NCs films with this procedure enabling smooth film morphologies to be obtained. 24 However, in the majority of devices the former method is utilized, referred to as solid-state ligand exchange, often inducing cracks and voids within the PbS NC films. To minimise these, PbS NCs films may be deposited via sequential layer-by-layer deposition and treatment (the same method also being employed for phototransistor and photodiode device fabrication).…”
Section: Pbs Nanocrystal Photodetectorsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]). Both reports in which sensitivity is given, as well as those from which it can be inferred, are included in this table.…”
Section: Quantitative Progress In Performancementioning
confidence: 98%